PENGARUH KARAKTERISTIK KEWIRAUSAHAAN, LOCUS OF CONTROL DAN GENDER TERHADAP KEBERHASILAN USAHA PADA HOME-BASED NEW VENTURES DI KELURAHAN API-API KOTA BONTANG - Nanda Agus Tina; Finnah Fourqoniah (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to examine and analyze the Effect of Entrepreneurial Characteristics, Locus Of Control, and Gender on Business Success in Home-based New Ventures in Api-api Village, Bontang City.This research is a quantitative research. The data collection technique in this study used a questionnaire with the number of respondents being 100 home-based new ventures entrepreneurs in Api-api Village, Bontang City. The analytical tool used is multiple linear regression analysis. Based on the results of the partial test, it shows that the characteristics of entrepreneurship and gender have a significant effect and locus of control has no significant effect on business success. However, the simultaneous test results show that the characteristics of entrepreneurship, locus of control, and gender have a significant effect on business success in home-based new ventures entrepreneurs in Api-api Village, Bontang City. The researcher gives suggestions that it is hoped that home-based new ventures entrepreneurs in Api-api Village, Bontang City can continue to apply entrepreneurial characteristics, can continue to apply internal locus of control and can apply gender indicators, namely roles, the same rights, benefits and control by improving the mindset. For further researchers, they can teach digital marketing considering that 69% of entrepreneurs in Api-api Village still do not have social media.